Front Cover: Magnetic Bistability in Macrocycle‐Based FeII Spin‐Crossover Complexes: Counter Ion and Solvent Effects (Eur. J. Inorg. Chem. 34/2016). Issue 34 (December 2016) - Milin, Eric; Benaicha, Bouabdellah; El Hajj, Fatima; Patinec, Véronique; Triki, Smail; Marchivie, Mathieu; Gómez‐García, Carlos J.; Pillet, Sébastien
Abstract : The cover picture shows the magnetic properties of a new series of Fe II spin‐crossover (SCO) complexes based on a N‐functionalized macrocycle ligand. One complex exhibits magnetic bistability with a 9 K wide hysteresis loop (136–145 K), whereas two others show an abrupt ( T 1/2 = 83 K) or gradual ( T 1/2 = 150 K) transition without hysteresis. These differences in behavior have been explained by the presence of strong, moderate, or weak intermolecular interactions mediated by the solvent (H2 O) and/or counter ions (shown to the left and right of the complex). Details are discussed in the article by S. Triki et al. onp. 5305 ff . For more on the story behind the cover research, see theCover Profile .